Friedman, Harsanyi, Rawls, Boulding - or Somebody Else? - Stefan Traub; Christian Seidl; Ulrich Schmidt; Maria Vittoria Levati (Kiel University, Department of Economics, 2003)
This paper investigates distributive justice using a fourfold experimental design : The ignorance and the risk scenarios are combined with the self-concern and the umpire modes. We study behavioral switches between self-concern and umpire mode and investigate the goodness of ten standards of behavior. In the ignorance scenario, subjects became on average less inequality averse as umpires. A within-subjects analysis shows that about one half became less inequality averse, one quarter became more inequality averse and one quarter left its behavior unchanged as umpires. In the risk scenario, subjects become on average more inequality averse in their umpire roles. A within-subjects analysis shows that half of them became more inequality averse, one quarter became less inequality averse, and one quarter left its behavior unchanged as umpires. As to the standards of behavior, several prominent ones (leximin, leximax, Gini, Cobb-Douglas) experienced but poor support, while expected utility, Boulding's hypothesis, the entropy social welfare function, and randomization preference enjoyed impressive acceptance. For the risk scenario, the tax standard of behavior joins the favorite standards of behavior.
urn:nbn:de:101:1-200910201801
Keywords: C91; D63; D31; 330; Distributive justice; income distributions; veil of ignorance; Verteilungsgerechtigkeit; Verhaltensökonomik; Experiment; Einkommensverteilung; Verfassungsökonomik; Theorie